2005
DOI: 10.2214/ajr.04.0729
|View full text |Cite
|
Sign up to set email alerts
|

MRI Versus Helical CT for Endoleak Detection After Endovascular Aneurysm Repair

Abstract: MRI is significantly superior to biphasic CT for endoleak detection and rating of endoleak size, followed by uniphasic late and uniphasic arterial CT scans. MRI shows a significant number of endoleaks in cases with negative CT findings and may help illuminate the phenomenon of endotension. Endoleak rates reported after endovascular aneurysm repair substantially depend on the imaging techniques used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…Pitton et al report sensitivity for endoleak detection of 92.9% for magnetic resonance imaging (MRI) versus 44% for biphasic CT in their follow-up study of 52 patients. 15 Van der Lean et al found that MRI detected endoleaks in 23 of 35 of the patients who they studied, compared with only 11 of the same group in whom endoleaks were detected by CTA. 16 Both authors conclude that MRI is significantly more sensitive than CTA for the detection of endoleaks.…”
Section: Discussionmentioning
confidence: 93%
“…Pitton et al report sensitivity for endoleak detection of 92.9% for magnetic resonance imaging (MRI) versus 44% for biphasic CT in their follow-up study of 52 patients. 15 Van der Lean et al found that MRI detected endoleaks in 23 of 35 of the patients who they studied, compared with only 11 of the same group in whom endoleaks were detected by CTA. 16 Both authors conclude that MRI is significantly more sensitive than CTA for the detection of endoleaks.…”
Section: Discussionmentioning
confidence: 93%
“…In several studies involving small numbers of patients with predominantly nitinol stents, MR angiography was at least as sensitive as CT angiography (131)(132)(133)(134)(135), and in some cases demonstrated endoleaks that were not detected on CT angiography. In one case report (136), endotension was suspected in two patients with enlarging aneurysm sacs and no endoleak on CT angiography, but a subsequent MR angiogram demonstrated type II endoleaks.…”
Section: Postoperative Surveillancementioning
confidence: 99%
“…43 Thus far, there have been several published studies of MR examinations in patients with aortic stent grafts that have not noted any adverse clinical events related to the MR examinations. 44,45 The MR characteristics of the Zenith AAA endovascular graft (Cook) have been evaluated through bench testing in MR systems with static fields of Յ1.5 T, and this stent graft was found to exhibit significant deflection and torque of the stainless steel metallic component of the endovascular graft and therefore did not meet standard "MR safe" bench test criteria. 46 A practical consideration in MR examinations of endovascular stents relates to the potential magnetic susceptibility effects (artifacts) induced by the metallic components of the stent grafts.…”
Section: Aortic Stent Grafts Background Datamentioning
confidence: 99%